Examination of the influences of the industrial attributes on the entry mode selection: case studies of the Coca-Cola Company from U.S entering the Chinese beverage industry and the BT Group plc from U.K entering the Chinese telecommunication industry. - Ma, Lingyu (2015)
The study has the purpose of examining the influences of industrial attributes, such as market structure and industrial policies, on the choice of entry mode for MNEs. It adopts the case study approach with two firms entering China, one is the Coca-Cola Company from the U.S and the other is the BT Group plc from the U.K, which enable us to see how the market structure, competition conditions, entry barriers and policies of these two different industries can influent the entry mode selection of those two firms. Moreover this study will also see what challenges they are facing in their respective industries and how they respond to them. At the end, I’ll also talk about the future inward FDI in China and the direction of the future research in this topic. For the findings of this study, I find that higher level of competition leads to the entry mode with more control, i.e. firms in the monopolistic competition market are more likely to choose wholly owned subsidiaries and those in oligopoly market would prefer joint ventures. To what extent that foreign firms can invest in a certain industry is much depends on the regulatory policies of that industry. The entry and operation strategy can be restricted within a limited scope by the government tight central control. In terms of responding to challenges, firms need to deal with the natural resource scarcity with a sustainable strategy that benefits both the firm itself and the host country, and be aware the knowledge of the local market, trying to adapt the products and services to local customers and comply with the industrial policies. Furthermore, comparing to Dunning’s eclectic paradigm, the internalisation advantages are not necessity for FDI and can be split into two extent, including internalisation of management and internalisation of technology. The findings from the study of these two cases mostly answer to the research questions.